2023
DOI: 10.1080/13880209.2023.2165114
|View full text |Cite
|
Sign up to set email alerts
|

Guilu-Erxian-Glue alleviates Tripterygium wilfordii polyglycoside-induced oligoasthenospermia in rats by resisting ferroptosis via the Keap1/Nrf2/GPX4 signaling pathway

Abstract: Context Guilu-Erxian-Glue (GLEXG) is a traditional Chinese formula used to improve male reproductive dysfunction. Objective To investigate the ferroptosis resistance of GLEXG in the improvement of semen quality in the oligoasthenospermia (OAS) rat model. Materials and methods Male Sprague-Dawley (SD) rats were administered Tripterygium wilfordii polyglycoside, a compound extracted from Tripterygium wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…When GPX4 is inhibited, ferroptosis will be triggered as the lethal amount of LPO accumulation. 50 Recently, both ACSL4 and GPX4-regulated ferroptosis has been found to participate in the pathological processes of CNS injuries. For example, in a mouse cerebral ischemia-reperfusion (I/R) injury model, the administration of baicalein inhibited the ferroptosis by the inhibition of ACSL4 and activation of GPX4.…”
Section: Discussionmentioning
confidence: 99%
“…When GPX4 is inhibited, ferroptosis will be triggered as the lethal amount of LPO accumulation. 50 Recently, both ACSL4 and GPX4-regulated ferroptosis has been found to participate in the pathological processes of CNS injuries. For example, in a mouse cerebral ischemia-reperfusion (I/R) injury model, the administration of baicalein inhibited the ferroptosis by the inhibition of ACSL4 and activation of GPX4.…”
Section: Discussionmentioning
confidence: 99%
“…The male and female SD rats (10 weeks of age) were ordered from Hunan Slyke Jingda Experimental Animal Co., LTD. The animals were raised in a temperature‐controlled chamber with a light and dark cycle of 12:12 h. [ 26 ] Male and female rats were caged by 2:1. Sperm was detected in the vaginal discharge test on the first day of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“… Factor/reagent Categories Mechanism Ref. Busulfan Drug Downregulated NRF2ˎGPX4 and FPN expression [ 70 ] Tripterygium wilfordii polyglycoside tablet Drug Inhibit NRF2/xCT/GPX4 axis and FPN espression [ 118 , 119 ] Ischemia-reperfusion Testicular torsion Downregulated NRF2ˎGPX4 and FPN expression [ 71 ] Scrotal hyperthermia High temperature exposure Increase ACSL4 expression [ 107 ] Smoking (nicotine) Habit Downregulated NRF2 and GPX4 expression [ 82 , 108 ] 2.5-micron particulate matter Environmental factor Depletion of GSH and reduce GPX4 expression [ 83 , 110 ] DEHP Environmental factor Increase TFR1 and HO1 expression Reduce GPX4 level [ 27 , 126 , 135 ] BisphenolA Environmental factor Downregulate NRF2/HO1 and xCT/GPX4 pathwayˎActivate ACSL4 expression and ROS accumulation [ 111 , 112 ] Arsenite Heavy mental Downregulate xCT/GPX4 pathwayˎInduce ROS release and increase iron levels [ 84 ] Cdmium Heavy mental Reduce FTHˎFPN and xCT expressionˎDownregulate NRF2/HO1 pathway and enhance lipid peroxidation [ 69 , 115 ] Hexavalent chromium Heavy mental Inhibit xCT/GPX4 and mTOR [ 99 ] Co...…”
Section: The Role Of Ferroptosis In the Testismentioning
confidence: 99%
“…Tripterygium wilfordii , a traditional Chinese medicine, is used to treat rheumatoid arthritis. However, the reproductive toxicity of Tripterygium wilfordii limits its clinical application, and its mechanism of reproductive toxicity is not fully understood [ 118 ]. Qin et al [ 119 ] combined metabolomics with transcriptomics and found that ferroptosis was associated with Tripterygium wilfordii -induced testicular injury.…”
Section: Ferroptosis In Male Reproductive Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation